ADHERENCE TO LEECH'S (2014) POLITENESS MAXIMS IN ILLOCUTIONARY SPEECH ACTS IN THE MINANGKABAU FILM ONDE MANDE! - Fatimah Azzahra; Djatmika; Miftah Nugroho (Lire Journal (Journal of Linguistics and Literature), 2026)
This study examines the forms of adherence to Leech's (2014) politeness maxims as realized through illocutionary speech acts in the Minangkabau regional film Onde Mande!. The study is motivated by the limited application of Leech's (2014) revised framework in existing literature, particularly in the context of regional Indonesian cinema. Employing a qualitative descriptive approach with a single case study design, this study draws on a pragmatic framework that integrates illocutionary speech act theory with Leech's (2014) politeness principles. Data were collected through non-participatory observation of the film's dialogue using note-taking and repeated playback techniques, and analyzed using the interactive model developed by Miles and Huberman (1994). The analysis identified 84 instances of politeness maxim adherence throughout the film's dialogue. From these data, 10 representative instances were selected for in-depth analysis. The findings reveal that seven of Leech's ten politeness maxims are present in the film's dialogue, namely the Generosity Maxim (M1), Tact Maxim (M2), Approbation Maxim (M3), Obligation of S to O Maxim (M5), Obligation of O to S Maxim (M6), Agreement Maxim (M7), and Sympathy Maxim (M9). These maxims are realized through four types of illocutionary speech acts, including expressive, directive, commissive, and assertive acts. The Tact Maxim and Obligation Maxims emerged as particularly prominent, reflecting the deeply rooted cultural values of respect, reciprocity, and communal harmony that characterize Minangkabau society. The study concludes that politeness adherence in the film is not limited to a single speech act type or social context, but manifests across varying interactional situations, ranging from family interactions to host-guest exchanges and community deliberations. The application of Leech's (2014) framework, as opposed to the earlier 1983 version, proves particularly valuable in capturing the full range of politeness forms present in the dialogue, especially through the differentiation of the Obligation maxims into M5 and M6. This study contributes to the growing body of research on linguistic politeness in regional Indonesian film and offers a replicable analytical model for future studies in this area.